Using WordNet-based Semantic Relatedness Measure for Reducing Redundancy and Improving Multi-document Text Summarization - Dam, Santanu; Sarkar, Kamal (International Journal of Computer Sciences and Engineering, 2025)
Multi-document text summarization (MDS) is a task to generate a single summary from a set of articles related to the same topic or event. Since each input article is related to the same topic or event, the generated summary contains redundant sentences or the sentences that contain almost similar information. This paper presents a sentence similarity measure for reducing redundancy in multi-document summary. Our proposed similarity measure combines the WordNet based semantic sentence similarity measure with the traditional cosine similarity measure. We have conducted our experiments using DUC 2004 benchmark multi-document summarization dataset to judge whether the proposed similarity measure is useful for redundancy removal and improving multi-document text summarization performance or not. Our experiments reveal that our proposed similarity measure is effective for reducing redundancy and improving multi-document text summarization performance